Superficial white matter: A review on the dMRI analysis methods and applications - Guevara, Miguel; Guevara, Pamela; Román, Claudio; Mangin, Jean-François (NeuroImage (Orlando, Fla.), 2020)
The mapping of human brain connections is still an on going task. Unlike deep white matter (DWM), which has been extensively studied and well documented, superficial white matter (SWM) has been often left aside. Improving our understanding of the SWM is an important goal for a better understanding of the brain network and its relation to several pathologies. The shape and localization of these short bundles present a high variability across subjects. Furthermore, the small diameter of most superficial bundles and partial volume effects induced by their proximity to the cortex leads to complex tratography issues. Therefore, the mapping of SWM bundles and the use of the resulting atlases for clinical studies requiere dedicated methodologies that are reviewed in this paper. •Superficial White Matter (SWM) is important to better understand the brain network and its relation to several pathologies.•We describe the main approaches used for the study of SWM based on diffusion MRI and some application examples.•A descriptive comparison between different diffusion models and tractography methods for the study of SWM is also included, as well as an analysis of short association bundle reproducibility, based on the state-of-the-art bundle atlases.